Gakkel Ridge Basalt Geochemistry (H2O, CO2, Cl, F, S, Ti) - Michael, Peter (IEDA: EarthChem Library, 2012)
Abstract: This dataset contain microprobe and FTIR data for H2O, CO2, Cl, F, S, Ti data for MORB from the Gakkel Ridge.